The Effect of Financial Distress, Internal Control, And Debt Structure on Earnings Management in Companies Registered in Indonesia Stock Exchange - Puspanagari Putri Ridanti; Diah Hari Suryaningrum (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
Earnings management is a manager's attempt to influence the information in the financial statements to trick stakeholders. Earnings management has two perspectives, namely positive and negative. If earnings management is practiced for a long period, it will be detrimental to the company. Managers have two main tools for performing earnings management: accrual earnings management and real earnings management. This study aims to test and prove the effect of financial difficulties, internal control, and debt structure on accrual and real earnings management. This research is quantitative by using multiple linear regression analysis methods. The sample selection used purposive sampling. The sample of this research is 28 manufacturing companies listed on the Indonesia Stock Exchange with five years of research, namely from 2015-2019. This research indicates that financial difficulties do not affect accrual earnings management but do affect real earnings management. Furthermore, this research suggests that companies experiencing greater financial difficulties carry out low real earnings management. Meanwhile, internal control and debt structure do not affect earnings management. The existing control variable only has an impact on the effect of debt structure on accrual earnings management.